Походження й семантичний розвиток назв заздрості в польській, російській та українській мовах - Ніколаєнко, Л.І. (Мовознавство, 2019)
У статті докладно проаналізовано погляди мовознавців щодо процесів становлення і розвитку підсистеми консонантизму протослов’янського діалекту праслов’янської мови у світлі загальних тенденцій розвитку праслов’янської фонологічної системи в цілому. Обґрунтовано важливість вивчення історико-фонологічних досліджень славістів із метою підвищення експланаторного рівня фонології та встановлення причинно-наслідкових ланцюгів, результатом яких стало формування фонологічної системи праслов’янської мови. The article is devoted to the study of the etymology and evolution of the semantics of the names of emotions of envy in the Polish, Russian, and Ukrainian languages. The article focuses on nouns and verbs. The names of envy in comparable languages were derived from semantically close Proto-Slavic verbs, meaning visual perception *viděti ‛see’ and *zьrěti ‛look’. The Ukrainian name ревнощі and Russian name ревность, in the semantic structure of which the seme ‛envy’ is present, does not have a single etymological version. An analysis of the lexicographic material suggests that from the point of view of the diachrony, the names of envy in the compared languages have been developed mainly in the direction from polysemantic to narrowing and concretization of meanings.